Emotionally intelligent organizations: exploring the impact of self-regulation, distress tolerance, and others’ emotion appraisal on workplace success (2024)
1. Introduction ; 2. Theoretical Background ; 3. Methodology ; 4. Demographic Results and Analysis ; 5. Discussion of Results.